(untitled) (Development Service Industry Management, 2024)
Modern theoretical and applied research aimed at analyzing current problems of managing the innovative activity of Ukrainian business is mainly focused on revealing its industry aspects and features. Increasing the innovative activity of domestic enterprises is an important factor in achieving the goals of the development of the national economy in the modern period, its post-war recovery and growth in the future. Disclosure of the mechanism for managing the innovative activity of enterprises based on the justification of its essential characteristics as a process of implementing the innovative function of business. Innovativeness is an essential feature of business, revealing its focus on the implementation of new ideas, technologies, products (services), the search for new markets, areas and areas of activity and is a basic condition for achieving a high level of its competitiveness and efficiency. Business innovativeness is potential, as the ability to innovate in various forms, and realized if its subjects are innovatively active. Therefore, the degree of realization of the innovative potential of a business depends on the innovative activity of its organizational units - enterprises, which necessitates the formation and implementation of an effective system of management of innovative activity, the task of which is to transform the innovative potential into real innovative projects, programs and activities. Innovative activity of an enterprise is the process of implementing the innovative function of a business, which determines the general orientation of the economic system to ensure business development based on innovations.